PENGEMBANGAN BAHAN AJAR M-PROR TENTANG PERAN PAHLAWAN SUKARNI KARTODIWIRYO UNTUK KELAS XI SMA - Nerry Supanji; Yuliati Yuliati; Lutfiah Ayundasari (Universitas Sultan Ageng Tirtayasa, 2021)
Some of the problems encountered by the author are as follows, (1) Lack of student independence in learning; (2) Utilization of technology and learning facilities is sometimes less precise than what students need; (3) Printed teaching materials must be purchased at school cooperatives; (4) At least reading about the character Sukarni Kartodiwirjo. This study aims to develop learning materials, test and determine the response of students' learning independence after operating the M-PROR. This research method uses the ADDIE model with the following stages: (1) needs analysis; (2) design and data collection; (3) product manufacture; (4) product validation and testing; (5) evaluation. The results of validation by media experts obtained a percentage of 90.95%, the results of validation by material experts were 94.47%, the results of validation by teachers were obtained by a percentage of 91.02%, the results of large trials obtained a percentage of 85.34%, and the student's learning independence response obtained a percentage of 83.47%. Based on the validation and trial data, the M-PROR teaching materials can be ascertained as follows: (1) research and product development can be completed properly according to the needs analysis; (2) overall the criteria are very feasible; (3) the level of student learning independence is obtained with very positive criteria. The M-PROR teaching materials were further developed by discussing other figures in the proclamation event in depth.